Complete mitochondrial DNA genome of Thryssa dussumieri (Valenciennes, 1848). Issue 1 (2nd January 2019) - Zhang, Jing; Zhang, Nan; Li, Yuan; Zhang, Ran; Lin, Longshan
Abstract: In this study, the complete mitochondrial genome (mitogenome) sequence of Thryssa dussumieri was determined by long polymerase chain reaction and primer walking methods. The mitogenome was a circular molecule of 16, 883 base pairs (bp) in length and contained 13 protein-coding genes (PCGs), 2 ribosomal RNA (rRNA), 22 transfer RNA (tRNA), and a control region similar to those found in other bony fishes. The overall nucleotide composition was estimated to be 32.1% A, 26.1% C, 23.7% T, and 18.1% G. The neighbor-joining tree was reconstructed based on the 13 PCGs sequences of T. dussumieri and other 10 Engraulidae species. The mitogenome data will provide useful information for further studies on the phylogenetic analysis and population genetics.